2011
DOI: 10.3109/17483107.2011.580900
|View full text |Cite
|
Sign up to set email alerts
|

Distinct tilting behaviours with power tilt-in-space systems

Abstract: Given the limited pressure relief compliance, alternative approaches to pressure relief and improved training may be needed for some clients. Wheelchair design and prescriptions may also need to reflect participants' preferences for sitting in small and medium tilts and changing position frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 14 publications
4
38
1
Order By: Relevance
“…Despite the limited PRs, WSs were performed closer to twice per hour for many subject days. This behavioral characteristic is very consistent with the reported activities of participants using their powered wheelchairs' tilt-in-space feature, whereby small tilts were performed two to three times per hour, but large tilts were rarely performed [30,32]. In previous work, we demonstrated that intermediate leans, which reduced pressure between 29 and 46 percent, resulted in increased blood flow on the order of 100 to 300 percent [17].…”
Section: Ws Frequencysupporting
confidence: 72%
See 1 more Smart Citation
“…Despite the limited PRs, WSs were performed closer to twice per hour for many subject days. This behavioral characteristic is very consistent with the reported activities of participants using their powered wheelchairs' tilt-in-space feature, whereby small tilts were performed two to three times per hour, but large tilts were rarely performed [30,32]. In previous work, we demonstrated that intermediate leans, which reduced pressure between 29 and 46 percent, resulted in increased blood flow on the order of 100 to 300 percent [17].…”
Section: Ws Frequencysupporting
confidence: 72%
“…As expected, larger movements are typically done with a lower frequency than smaller movements. At this time, studies of the sitting behavior of wheelchair users have been limited to measurement of occupancy [29][30][31][32][33] or complete off-loadings [33][34][35] and a single pilot study that considered smaller movements but was never expanded to a full study [36].…”
Section: Introductionmentioning
confidence: 99%
“…Sonenblum et al [18] conducted a longitudinal monitoring study in which only 1 out of 16 wheelchair users tilted beyond 30° at least once daily. Their follow-up study [20] found that the participants tilted beyond 30° less than once per day on average. Yet, when asked to identify, verbally describe, and physically demonstrate various pressure-relieving maneuvers, roughly three-quarters of the participants succeeded.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…However, as the number of monitored wheelchair users grows larger, this data collection and retrieval routine may become more and more unmanageable due to the increased overhead in manpower and time. Furthermore, as with all observational studies, there are concerns of observer-expectancy bias in which participants may alter their natural behaviors because they are being recorded [20,21]. Thus, reducing how often the participants are reminded of the monitoring process (e. g. , reducing the frequency of data retrieval) may also help in the effort to understand true behaviors in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…As TIS has become more available on EPIOCs (and less expensive), it may be prescribed more frequently, offering greater comfort 13 , improved pressure relief 36 and relieving fatigue in conditions like MS.…”
Section: Equipmentmentioning
confidence: 99%